Transient elastography using Fibroscan is the most reliable noninvasive method for the diagnosis of advanced fibrosis and cirrhosis in alcoholic liver disease. Issue 9 (September 2015) - Fernandez, Michael; Trépo, Eric; Degré, Delphine; Gustot, Thierry; Verset, Laurine; Demetter, Pieter; Devière, Jacques; Adler, Michael; Moreno, Christophe
Abstract : Objective: Fibroscan (FS) is a reliable noninvasive method for the diagnosis of advanced fibrosis and cirrhosis in chronic liver disease. However, there is no clear consensus with respect to the best FS cut-off values for use in alcoholic liver disease (ALD). The aims of this study were as follows: (a) to compare the performance of FS and different biochemical markers in ALD patients; (b) to assess the best FS cut-off values for the prediction of fibrosis stage in our ALD population; and (c) to assess the influence of aspartate aminotransferase (AST) values on FS. Patients and methods: This retrospective study included 135 consecutive and compensated ALD patients who underwent liver biopsy between November 2006 and March 2012 at Erasme Hospital. FS, Fibrotest, FIB-4, aspartate aminotransferase to platelet ratio index (APRI), and Forns' scores were tested in all patients. Results: The diagnostic accuracy of FS was 0.89 (95% confidence interval: 0.83–0.95) for the diagnosis of advanced fibrosis and 0.93 (95% confidence interval 0.90–0.97) for the diagnosis of cirrhosis. FS performed better than Fibrotest (0.81 and 0.88), APRI (0.65 and 0.75), Forns' (0.64 and 0.78), and FIB-4 (0.70 and 0.73). The optimal cut-off values of liver stiffness (LS) for predicting METAVIR fibrosis stage F≥3 and F4 disease were 10.3 and 18.0 kPa, respectively. AST showed a significant positive correlation with LS ( r =0.24, P =0.001). However, exclusion of patients with AST more than 50 IU/l only lowered the LS cut-off for the diagnosis of F4 (14 vs. 18.0 kPa). Conclusion: FS is currently the most reliable noninvasive method for the diagnosis of advanced liver fibrosis and cirrhosis in ALD. Abstract : Supplemental Digital Content is available in the text.